Podocyte density and albuminuria in aging diabetic ins2± mice with or without adenosine a1 receptor signaling - Faulhaber-Walter, Robert; Jiang, Lanping; Mizel, Diane; Zerfas, Patricia M.; Kopp, Jeffrey B.; Schnermann, Jurgen B.; Chen, Limeng; Schiffer, Mario (International Journal of Nephrology and Renovascular Disease, 2020)
Aim of Study: To investigate podocyte density in aging diabetic Ins2± and Ins2±, A1AR-/-mouse models in C57Bl/6 background. Methods: Ins2± mice and especially Ins2±, adenosine A1 receptor knockout mice (Ins2±, A1AR-/-) are mouse models with a phenotype of diabetic nephropathy. Aged mice (at 40 weeks) were assessed for glomerular filtration barrier function by measuring albuminuria, glomerular filtration, glomerular damage by electron microscopy, and podocyte numbers by Wilms Tumor protein (WT-1) staining. Results: Compared to healthy wild-type mice, both diabetic mouse models developed diabetic nephropathy, including hyperfiltration (p<0.01) and albuminuria (p<0.05). Typical diabetic structural glomerular and podocyte damage was visualized by electron microscopy. Podocyte count per glomerular area (podocyte density) was significantly decreased in both diabetic mouse models (p<0.01). In contrast, no significant correlation was detected between albuminuria and absolute podocyte count per glomerulus. Conclusion: The amount of albuminuria as marker of diabetic nephropathy does not correlate with the podocytes density; however, a relative podocyte deficiency became evident with an increase in glomerular area in the diabetic animals, suggesting a relative podocytopenia.
CRIS-Team Scopus Importer:2020-03-06
Keywords: Diabetes nephropathy podocyte mouse Akita WT-1